Modulation Techniques in Translation of Critical Eleven by Ika Natassa - Siregar, Sarah Mia Angella; Zuindra; Geubrina, Misla (International Journal Linguistics of Sumatra and Malay, 2023)
The purpose of this study is to find out the types of modulation technique, to analyze the modulation technique works and the dominant type of modulation technique in the Critical Eleven novel by Ika Natassa. The method of this research was descriptive qualitative. Data were collected from sentences that consist of words, phrases, and clauses in the novel Critical Eleven as source of data. The findings of the study revealed that: (a) all the modulation techniques proposed by Vinay and Dalbernet (1995) were used in the Critical Eleven novel by Rain Chudori as the translator, which are: abstract for concrete, reversal of terms, negative contrary, part to whole, part another part, active for passive, space for time, intervals and limits, and change of symbol, (b) modulation techniques were used by changing the form or structure of a sentence without altering its meaning, and (c) there are two most dominant techniques in the novel, which are: abstract for concrete three data found and reversal of terms three data found.